2005
DOI: 10.1583/04-1447r.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mechanical Thrombectomy Device to Recanalize a Subacutely Occluded Aortohepatic Bypass After Orthotopic Liver Transplantation

Abstract: The Rotarex thrombectomy system may be considered an alternative to other percutaneous interventions for the treatment of occluded bypass conduits supplying a liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thrombosis of the hepatic artery and the conduit remains the major problem. [9][10][11][12][13] We believe that meticulous surgical technique, aggressive surveillance, and early intervention are very important in preventing and treating this complication. We also by policy place such recipients on salicylic acid (80 mg once daily) as prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the hepatic artery and the conduit remains the major problem. [9][10][11][12][13] We believe that meticulous surgical technique, aggressive surveillance, and early intervention are very important in preventing and treating this complication. We also by policy place such recipients on salicylic acid (80 mg once daily) as prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no HA thrombosis or stenosis was observed during the follow-up period. Thrombosis of the HA and the aortohepatic conduit remains the major problem [ 23 25 ]. We believe that a meticulous surgical technique and aggressive surveillance are crucial in preventing this complication, in addition to prophylactic therapies such as acetylsalicylic acid and other post-transplantation medications [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the hepatic artery and the conduit remains the major problem 9–13. We believe that meticulous surgical technique, aggressive surveillance, and early intervention are very important in preventing and treating this complication.…”
Section: Discussionmentioning
confidence: 99%